Analisis Kelistrikan Sel Volta Memanfaatkan Logam Bekas - Devi Yulianti; Amir Supriyanto; Gurum Ahmad Pauzi (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2017)
It has been conducted a research to analyze the scrap metals as voltaic cells. The research objective was to utilize scrap metals as an alternative source of electrical energy and as a voltaic cell to the battery. The materials required consist of a electrode copper (Cu), iron (Fe), aluminum (Al) and zinc (Zn), solution of CuSO4.5H2O, solution of ZnSO4.7H2O, solution of Al2(SO4)3.7H2O, solution of FeSO4.8H2O, jelly powder, and salt NaCl. The electrode couple are Cu-Al, Cu-Fe, Cu-Zn, Al-Zn, and Fe-Zn. Volume variation are 20 ml, 25 ml, 30 ml, 35 ml, and 40 ml. Data of the voltage and current taken using a multimeter on each cell, without a load, with a load, and additional load. The results of the research were analyzed the value of power, current, and voltage with the greatest results in Cu-Zn electrode pair. The results are 14,949 mW, 3,05 mA, and 4,96 V.